Transoral outlet reduction: could additional sutures cause more harm? - Farha, Jad; Gebran, Selim; Itani, Mohamad I.; Simsek, Cem; Abbarh, Shahem; Lopez, Ariana; Haq, Zadid; Koller, Kristen; Dunlap, Margo; Adam, Atif; Khashab, Mouen A.; Oberbach, Andreas; Schweitzer, Michael; Badurdeen, Dilhana; Kumbhari, Vivek (Endoscopy, 2021)
Background The double purse-string pattern (DPSP) of transoral outlet reduction (TORe) should conceivably result in a more robust scaffolding for the gastrojejunal anastomosis (GJA). However, there is a paucity of literature pertaining to post-TORe stenosis as an adverse event. Our aim was to determine the rate of stenosis, its potential predictors, and other complications of DPSP TORe.Methods We performed a retrospective analysis of a prospectively maintained database of 129 consecutive patients who underwent DPSP TORe between December 2015 and August 2019.Results The adverse event rate of TORe was 17.1 % (n = 22), with a 13.3 % (n = 17) rate of stenosis. Stenosis was not significantly associated with any baseline characteristics. GJA diameter pre- and post-TORe, the difference between these values, and procedure duration were not predictive of stenosis. Of patients who developed stenosis, 10 (58.8 %) responded to endoscopic balloon dilation and 7 (41.2 %) required stent placement.Conclusion As the DPSP technique is a challenging procedure, with high complication rate and limited benefit, it should not be used for TORe.